Effects of Parsley (Petroselinum crispum) Extract and Glibornuride on the Kidney of Streptozotocin- Induced Diabetic Rats - KOYUTURK, MERAL; OZSOY-SACAN, OZLEM; YANARDAG, REFIYE; BOLKENT, SEHNAZ (Asian Journal of Chemistry, 2010)
The purpose of this study was to investigate the effect of parsley (Petroselinum crispum) extract and compare the effects with a hypoglycemic agent glibornuride on the kidney as histological and biochemical in normal and streptozotocin-induced diabetic rats. The parsley extract was administered by gavage technique to rats a dose of 2 g/kg daily for 28 d; 14 d after experimental animals were made diabetic. 5 mg/kg glibornuride were given by same method, 14 d after the experimental animals were made diabetic, to one of the diabetic group and also one of the control group, daily for 28 d. The kidney tissues were examined histologically, blood glucose, serum urea and creatinine levels were determined, spectrophotometrically. The distinct degenerative changes were observed in the kidney tissue of streptozotocin-induced rats. On the other hand, the injury to kidney tissue was minimal or absent in diabetic group given parsley extract. The damage of kidney tissue was minimal in streptozotocin induced group given glibornuride. Blood glucose, serum urea and creatinine levels significantly increased in diabetic groups. Administration of parsley extracts and glibornuride significantly reduced blood glucose, serum urea and creatinine levels in diabetic groups. According to these results, it is concluded that parsley extract is more effective in comparison to glibornuride in the protection of kidney tissue from the damage of streptozotocin induced diabetic rats.